Creating a Nationalist Conservative Intellactuals: The Case of Adana People’s House - Güldal, Mehmet (Fırat University, 2024)
The mantra of a new homeland, a new society, a new state, in which Kemalist republicanism manifested itself, corresponds to such a moment of transformation. The emergence of a brand-new regime comes with a specific ideological program. Thus, Kemalism is the name of this ideological program following the Turkish War of Independence. Yet, the mere exposition of an ideological program is not enough on its own. In this respect, Kemalism needs to unify society around its ideological program. Hence, the need for an intellectual class has arisen. In order to facilitate social mobilization around the Kemalist doctrine, there was a necessity to organize educators and nurture new generations. The ideological background that shaped all this policy-making developed under the very influence of the corporatist vision. An important function is attributed to these social organizations shaped by corporatism. This paper will question the function of the Halkevi, which were established as corporatist social bodies under the One-Party rule, in the formation of new generations. The paper will also investigate how the nationalist conservative figures raised in Adana Halkevi evolved into anti-communist intelligentsia, subsequent to the transition to Multi-Party Life.

Kemalist Cumhuriyetçiliğin kendisini gösterdiği, “yeni vatan, yeni sosyete, yeni devlet” şiarı, böyle bir dönüşüm anına tekabül etmektedir. Yeni bir rejimin ihdas edilmesi, belirli bir ideolojik programla birlikte gelmektedir. Kemalizm, Millî Mücadele sonrası bu ideolojik programın adıdır. İdeolojik programın ortaya konması tek başına yeter değildir. Bu nedenle, Kemalizmin toplumu ideolojik programı etrafında bütünleştirilmesi gerekmektedir. Böylece, aydın sınıfa olan ihtiyaç ortaya çıkmıştır. Toplumsal mobilizasyonun, Kemalist doktrin etrafında şekillenebilmesi için eğiticilerin organize edilmesi ve yeni nesillerin yetiştirilmesine ihtiyaç duyulmuştur. Bu bağlamda kurulan, ocaklar ve evler bu yeni kuşağın üretimi ve Cumhuriyet’in devamlılığını sağlama idealiyle teşkilatlandırılmıştır. Bütün bu siyasa üretimini kesen, ideolojik arka plan korporatist dünya görüşünün etkisinde gelişmiştir. Korporatizmle şekillenen bu sosyal teşekküllere çalışmada önemli bir işlev atfedilmektedir. Bu çalışmada, Tek Parti yönetimi altında “korporatist sosyal teşekkül” olarak oluşturulan Halkevlerinin yeni nesillerin yetiştirilmesi konusunda hangi işlevi yerine getirdiği sorgulanacaktır. Çalışmada ayrıca, Çok Partili Yaşam’a geçiş sonrasında, Adana Halkevi’nde yetişen milliyetçi muhafazakâr isimlerin nasıl anti-komünist entelektüellere dönüştüğü incelenecektir.
MİLLİYETÇİ MUHAFAZAKÂR ENTELEKTÜELİ YARATMAK: ADANA HALKEVİ ÖRNEĞİ
Keywords: Arts and Cultural Policy; Sanat ve Kültür Politikası